Assessment of ipsilateral and contralateral perfusion after contrast compression therapy of upper limb muscles in MMA athletes - a cross-over study - Robert Trybulski; Robert Trybulski; Arkadiusz Stanula; Jarosław Muracki; Wacław Kuczmik; Ahmet Kurtoğlu; Jakub Taradaj (Frontiers in Physiology)
ObjectiveThe primary aim of this study was to compare the immediate effect of contrast compression therapy with the use of Game Ready (GRT) on hyperaemic reactions in the upper limb on the application and contralateral sides, specifically in the context of mixed martial arts (MMA) athletes.DesignIn this experimental, single-blind, randomized crossover study, we recruited 30 male volunteers training in MMA (mean age: 28.33 ± 3.79 years, BMI: 25.25 ± 3.06, training experience: 9.93 ± 3.83). They were randomly assigned to the experimental (n = 15) or control (sham) group (n = 15). The experimental group underwent a 10-minute Game Ready Therapy (GRT) session, while the control group GRS underwent a sham therapy session. After a 2-week break, a cross-over change of therapy in the groups was performed, ensuring a comprehensive evaluation of the contrast compression therapy’s perfusion effects in 30 participants. Main outcome measures: Hyperemic reaction was measured: rest flow (RF - [non-referent unit]); therapeutic flow (TF- [min]), i.e., the average flow recorded during GR or sham therapy: time of recovery (TR - [min]), i.e., the time for perfusion to return to the resting value after the intervention. Measurements were performed on the ipsilateral and contralateral sides.ResultsThe mean perfusion during therapy was significantly higher in GRT compared to GRS (24.70 ± 1.45 vs. 12.60 ± 1.37; p < 0.001; ES = 5.7 [large]; △ = 12.10 > MDC). The time from cessation of contrast therapy to the return of blood flow to resting values showed significantly higher values in GRT compared to GRS (3.07 ± 0.45 vs. 16.80 ± 0.91; p < 0.001; ES = 16.27 [large]). No statistically significant difference was noted between the mean resting perfusion value (RF) and the mean perfusion value during therapy (TF) in the contralateral limb (7.74 ± 0.89 vs. 7.66 ± 0.89; p = 0.284; ES = 0.20 [negligible]; △ = 0.09 < MDC.ConclusionThis study suggests that compression contrast therapy on the ipsilateral side positively affects the intensification of the hyperaemic reaction. However, no statistically significant hyperaemic responses were observed on the contralateral side.